PENDEKATAN GAYA PENYUTRADARAAN ITALIAN NEOREALISME DALAM FILM PENDEK “KALA RAU: HARI INI MATAHARI PERGI BERSEMBUNYI” - I Wayan Medy Mahasena; Nyoman Lia Susanthi; Made Rai Budaya Bumiarta (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Every film has its own concept or characteristic, whether it's the characteristics of the director or writer scenario. The application of these directing characteristics can make an impression on the audience by remembering the uniqueness of a film and the uniqueness of the film. A characteristic can be channeled through a concept. This is what motivated the author to apply the concept of Italian neorealism in the making of the short film “Kala Rau: Hari Ini Matahari Pergi Bersembunyi”. As a form of directing style that is close and represents the vision and mission that the author wants to convey to the audience. The short film “Kala Rau: Hari Ini Matahari Pergi Bersembunyi”tells the story of Sri a child who has lost his father since he was young and has a curiosity about the cause of his father's departure. Sri accompanied by Ketut began his search for his father when a solar eclipse occurred. On the way, Sri finds many things that are blocking her father's absence. The method applied in the implementation of the directing style Italian neorealism which is emphasized in its application is the selection of roles, the structure of the story packaging, and the selection of shooting locations. The results of this creation show that the overall application of the directing style is Italian neorealism able to present an educative message from the short film “Kala Rau: Hari Ini Matahari Pergi Bersembunyi”.